High-Performance Virtual Reality Volume Rendering of Original Optical Coherence Tomography Point-Cloud Data Enhanced With Real-Time Ray Casting - Maloca, Peter M; de Carvalho, J. Emanuel Ramos; Heeren, Tjebo; Hasler, Pascal W; Mushtaq, Faisal; Mon-Williams, Mark; Scholl, Hendrik P.N.; Balaskas, Konstantinos; Egan, Catherine; Tufail, Adnan; Witthauer, Lilian; Cattin, Philippe C. (Translational vision science & technology, 2018)
Feasibility testing of a novel volume renders technology to display optical coherence tomography data (OCT) in a virtual reality (VR) environment. A VR program was written in C++/OpenGL to import and display volumetric OCT data in real time with 180 frames per second using a high-end computer and a tethered head-mounted display. Following exposure, participants completed a Simulator Sickness Questionnaire (SSQ) to assess for nausea, disorientation, and oculomotor disturbances. A user evaluation study of this software was conducted to explore the potential utility of this application. Fifty-seven subjects completed the user testing (34 males and 23 females). Mean age was 48.5 years (range, 21-77 years). Mean acquired work experience of the 35 ophthalmologists (61.40%) included in the group was 15.46 years (range, 1-37 years). Twenty-nine participants were VR-naïve. The SSQ showed a mean total score of 5.8 (SD = 9.44) indicating that the system was well tolerated and produced minimal side effects. No difference was reported between VR-naïve participants and experienced users. Overall, immersed subjects reported an enjoyable VR-OCT presence effect. A usable and satisfying VR imaging technique was developed to display and interact with original OCT data. An advanced high-end VR image display method was successfully developed to provide new views and interactions in an ultra high-speed projected digital scenery using point-cloud OCT data. This represents the next generation of OCT image display technology and a new tool for patient engagement, medical education, professional training, and telecommunications.